ANALISIS HUBUNGAN KUALITAS PELAYANAN KEFARMASIAN TERHADAP KEPUASAN PASIEN RAWAT JALAN RUMAH SAKIT UMUM SEMBIRING TAHUN 2021 - Anggun Syahfitri (Jurnal Penelitian Kesmasy, 2021)
Patient satisfaction is a leading indicator of service success that affects satisfaction in pharmaceutical services. If the service is in accordance with expectations, of course the quality of service is considered good and satisfactory, otherwise the service received is not satisfactory then the quality of service is considered bad. The purpose of this study was to analyze the relationship of physical evidence, reliability, responsiveness, assurance, and empathy to the satisfaction of outpatients of Sembiring general hospital. The type of research used mix methods with cross sectional design on quantitative research and sequential explanatory strategy on qualitative research. The population were 1160 people, with a sample of 92 people obtained using purposive sampling. Data collection in quantitative research by means of questionnaire dissemination while in qualitative research by way of indept interview. The results of the study obtained variables related to the satisfaction of outpatients of sembiring general hospitals, namely: Physical evidence (p value = 0.003), Reliability (p value = 0.001), Responsiveness (p value = 0.003), Guarantee (p value = 0.005), and Empathy (p value = 0.000). The results in depth interview found that the variable most associated with patient satisfaction was empathy. It is recommended to The Outpatient Pharmacy of Sembiring General Hospital to maintain a good quality of service and continue to improve the quality of service to patients.